The Effect of Soil Amendments and Shading on the Yield of Red Chili (Capsicum annum L.) in a Sandy Dryland - Lalu Wahyu Ardis Pandya; I Komang Damar Jaya; Bambang Budi Santoso; Jayaputra (Jurnal Penelitian Pendidikan IPA, 2024)
Low nutrient along with intense sunlight levels in sandy drylands, often lead to poor crops yield. This study examined the effects of soil amendments and shading on the yield of red chili plants cultivated in a sandy (70% sand, 15% clay and 15% silt) dryland environment. The experiment was conducted in Gumantar Village, North Lombok Regency from May to September 2024. The C-organic content of the soil was 1.11% with only 0.09% of total nitrogen. The soil amendment treatments included no soil amendment, chicken manure, and seaweed biochar. The shading treatments consisted of two levels: no shading and shading using a 200-micron UV plastic with 14% diffusive ultraviolet ray. All treatments were arranged factorially using a randomized block design with three replications. The results indicated that soil amendments and shading did not significantly affect plant growth, certain soil chemical properties, or microbial populations, possibly due to its short time effect. However, both types of soil amendments and UV plastic shading increased the yield of red chili plants by approximately 6.0% compared to the treatment without any amendments or without shading. This study shows that soil amendment and shading with UV plastic improve tomato yield in sandy dryland soils.